Pegada hídrica para a bacia hidrográfica do Rio Itapemirim - Leal, Ana Paula Porto Neves (2016)
The search for a better water management has been based on the current issues around reducing its availability and quality. The use of indicators on water consumption is one of the most important tools for this management. In this context, water footprint (PH) is a new concept of consumption of freshwater that considers its direct and indirect use by a consumer or producer, being used as a comprehensive indicator of the appropriation of water resources, and also assesses water use sustainability. The pH is subdivided into blue, which corresponds to the available fresh water, both surface and underground; green water, which is rainwater that is retained in plants and soil; and gray water, quantity of water used for dilution of pollution of activities in the basin. This study aimed to evaluate the pH of the basin of the river Itapemirim. The evaluation of PH consisted of distinct phases: definition of objectives and scope, accounting for PH and sustainability assessment of PH in the basin. They were considered the main water user sectors in the Itapemirim river basin: agriculture, livestock, forestry, supply, and urban sanitation. The total water footprint of the Itapemirim River basin was 6.4 billion cubic meters / year, considering that the largest contribution was given by the green water, with 92% of the total PH, followed by gray water, with 7%, and blue water, with 1%. Regarding the classes of the basin user sectors, the agricultural class, especially the component green water, was the class that consumed more freshwater in the basin. A green footprint is unsustainable from an environmental point of view, reaching high levels of green water scarcity as 2.59 in July. The blue and gray footprints were considered sustainable in the basin, the largest index of blue water shortage equal to 79%. The addition of forest cover on bowl 8%, 10% and 15% increased by 0,19%, 0,24% and 0,36% respectively of the total PH.